The Abundance of Leptophryne javanica in the Streams of Mount Ciremai National Park - Aprilianti, Risma; Kusrini, Mirza Dikari; Mardiastuti, Ani (Media Konservasi, 2025)
Leptophryne javanica is a frog in West Java and Central Java. Threats to the presence of L. javanica in nature include volcanic activity and chytrid fungi. The population of L. javanica is not known for certain. This study aims to estimate the abundance of L. javanica in several streams of Mount Ciremai National Park and describe the habitat of this species. This research was conducted in Cisurian Waterfall, Cilutung Waterfall, Ciinjuk Spring, and Cilengkrang Waterfall using visual encounter methods combined with sampling transect. L. javanica was found mostly in Ciinjuk Springs with an abundance of 2.50 ± 3.09 ind /10 m. More males were found than females, except in the Cisurian Waterfall. The body size and weight of the females were larger than the males. The microhabitat of Ciinjuk Spring had an average of river currents of 0.34 m/s, river width of 0.8–1.2 m, river depth of 1.0–3.4 cm, and canopy density ranging from 54.17–100%. In addition to the spring, the waterfall was also a preferred habitat by L. javanica. Further research is needed in other waterfalls and rivers with microhabitat characteristics similar to Ciinjuk Spring.